Nano Coating of Aloe-Gel Incorporation Additives to Maintain the Quality of Freshly Cut Fruits - Luh Suriati (Frontiers in Sustainable Food Systems, 2022)
The edible coating is an environmentally friendly technology that is applied to fresh-cut fruit products. One of the natural ingredients that are potentially applicable is aloe-gel because it contains several functional components. The main advantage of aloe-coating is that additives can be incorporated into the polymer matrix to enhance its properties. Additives tend to improve the safety, nutritional, and sensory attributes of fresh fruits, but in some cases, aloe-coating does not work. Furthermore, particle size determines the effectiveness of the process on fresh-cut fruits. Aloe-gel nano-coating can be used to overcome the difficulty of adhesion on the surface of fresh-cut fruits. However, quality criteria for fresh cut fruit coated with aloe-gel nano-coating must be strictly defined. The fruit to be processed must be of minimal quality so that discoloration, loss of firmness, spoilage ratio, and fruit weight loss can be minimized. This study aims to discuss the use of nano-coating aloe-gel incorporated with additional ingredients to maintain the quality of fresh-cut fruits. It also examined the recent advances in preparation, extraction, stabilization, and application methods in fresh fruits.